Treponema pallidum-specific antibody expression for the diagnosis of different stages of syphilis - SUN, Ran; LAI, Di-hui; REN, Rong-xin; LIAN, Shi; ZHANG, Hai-ping (Chinese medical journal, 2013)
Background Tp15, Tp17, Tp45, and Tp47 are outer-membrane proteins found in Treponema pallidum, the etiologic agent of syphilis. These proteins are potent antigens and are potential markers for the serological detection of syphilis. The present study analyzed antibodies to these protein antigens （TP-IgM and TP-IgG） in human serum and investigated the expression of these antibodies during different stages of syphilis. Methods Serum samples were collected from 69 subjects （male 45, female 24） diagnosed with syphilis and analyzed by Western blotting for the expression of IgM and IgG against the four protein antigens. Expression levels of the target antibodies were compared during the same stage of syphilis as well as between different stages of this disease. Results In subjects with primary syphilis, the positive rate of Tp45 IgM was higher than that of other TP-IgM. Tp15 IgM was detected only in subjects with tertiary syphilis. Similarly, the seroprevalence of Tp45 IgG in primary syphilis was higher than for other TP-IgG. No target TP-IgM was detected in subjects with latent syphilis. In subjects with secondary syphilis, the expression level of Tp15 IgG （138.73±20.16） was higher than for other target TP-IgG. In subjects with tertiary syphilis, all target TP-IgG were detected. In subjects with tertiary or latent syphilis, the expression levels of Tp45 IgG （121.33±11.04 and 110.10±40.19, respectively） were higher than those of other target TP-IgG. The expression levels of all Tp-lgM were similar before or after anti-syphilis treatment. In comparison, the expression levels of all TP-IgG decreased compared with the pre-treatment levels, and this decrease was statistically significant （both P 〈0.05） for Tp17 IgG and Tp47 IgG. Conclusions After Treponema pallidum infection, Tp45 IgM appeared first and Tp15 IgM occurred during later stages. The positive rates of all TP-IgG increased with the duration of this disease. Anti-syphilis treatment reduced the expression levels of Tp17 IgG and Tp47 IgG. Larger-scale studies are required to further validate the value of Tp15, Tp17, Tp45, and Tp47 as markers for the early detection of primary and latent syphilis.